Meningkatkan Pengetahuan Siswa Dalam Permainan Olahraga Tradisional Dengan Metode Video Visual Di Smp Negeri 18 Kota Bengkulu - Andre Anggara (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
Traditional sports games are part of the nation’s cultural heritage, rich in educational, social, and cultural values. However, technological advancements and the dominance of modern games have shifted students’ interest away from traditional games. This study aims to analyze the effectiveness of the video visual method in improving students’ knowledge of traditional sports games, specifically Hadang, Bentengan, and Tap Jongkok, at SMP Negeri 18 Kota Bengkulu. This research employed a descriptive qualitative method, with data collected through observation, interviews, documentation, and knowledge tests (pretest and posttest). The subjects consisted of 100 students (50 male and 50 female). The learning process was conducted through educational video screenings, discussions, Q&A sessions, and direct field practice. The results showed that the students’ average pretest score was 62.4 (Poor category), while the posttest average increased to 82.6 (Good category), with an improvement of 20.2 points or 32.4%. Observations revealed a significant increase in learning focus (85%), discussion participation (80%), and practical involvement (90%). Interviews indicated that the video visual method helped students understand the material more clearly, made it easier to remember playing techniques, and sparked interest in playing traditional games again. This study concludes that the video visual method is effective in enhancing students’ knowledge of traditional sports games, while also supporting the preservation of local culture. It is recommended that PJOK teachers apply this method consistently with adequate school facilities.